Analysis of Critical Success Factors (CSF) in the Quality Assurance Project of PT. SVM - Arizia Aulia Aziiza; Karina Nine Amalia (Faculty of Computer Science, University of Jember, 2022)
A development project of quality assurance is always planned to achieve a successful and satisfactory final project result. Many factors affect a quality assurance project's ability to achieve a successful final project result, called the Critical Success Factors. Conducting critical success factor analysis requires the company appropriate for the research, PT. SVM was selected as the subject of research. This research analyzes the Critical Success Factors (CSF) at PT. SVM in handling university quality assurance development projects in various cities in Indonesia. The research stages are the initial interview, literature review, data analysis and verification, and determining the result. The results of the CSF analysis in the literature matched with the verification results of CSF-related interviews. Based on 25 CSFs analyzed from the literature review, 23 CSFs were used in PT. SVM and 2 CSFs were not obtained from the verification process at PT. SVM.